Observing Joint Action: Coordination Creates Commitment - Michael, John (Cognition, 2016)
Previous research has shown that interpersonal coordination enhances pro-social attitudes and behavior. Here, we extend this research by investigating whether the degree of coordination observed in a joint action enhances the perception of individuals’ commitment to the joint action. In four experiments, participants viewed videos of joint actions. In the low coordination condition, two agents made independent individual contributions to a joint action. In the high coordination condition, the individual contributions were tightly linked. Participants judged whether and for how long the observed agents would resist a tempting outside option and remain engaged in the joint action. The results showed that participants were more likely to expect agents to resist outside options when observing joint actions with a high degree of coordination. This indicates that observing interpersonal coordination is sufficient to enhance the perception of commitment to joint action.